Phylogeography and genetic diveristy of two neotropical fish species shared between Orinoco and Amazon basins : evaluating connectivity and current and historical patterns (2017)
"The aim of this study is to determine the genetic diversity and its distribution in two freshwater species shared between the Orinoco and Amazon basins: Dourada (Brachyplatystoma rousseauxii) and Cardinal tetra (Paracheirodon axelrodi), which are overexploited for ornamental and consumer use, by analyses of mtDNA and microsatellite markers. Results from this study will provide scientific knowledge useful for fisheries management and conservation. This study will contribute to the understanding of factors and events involved in structuring the populations and distribution patterns in fish species with high commercial value for the Amazon and Orinoco region. Furthermore, this study will provide the first phylogeographic and population structure information of P. axelrodi and B. rousseauxii in the Orinoco basin, since studies of both species have been done only in the Amazon basin. Additionally, this study will provide support regarding other possible routes of connectivity between basins and information about possible protected areas that could be defined as well as identify fish populations that may require actions for their conservation and sustainable usage." Página 3